Measurement of prompt J/ψ and beauty hadron production cross sections at mid-rapidity in pp collisions at √s=7 TeV - Abelev, Betty; Adam, Jaroslav; Adamova, Dagmar; Adare, Andrew Marshall; Aggarwal, Madan; Rinella, Gianluca Aglieri; Agocs, Andras Cabor; Agostinelli, Andrea; Salazar, Saul Aguilar; Ahammed, Zubayer; Ahmad, Arshad; Ahmad, Nazeer; et al. (SPRINGER, 2012)
The ALICE experiment at the LHC has studied J/psi production at mid-rapidity in pp collisions at root s = 7 TeV through its electron pair decay on a data sample corresponding to an integrated luminosity L-int = 5.6 nb(-1). The fraction of J/psi from the decay of long-lived beauty hadrons was determined for J/psi candidates with transverse momentum p(t) > 1,3 GeV/c and rapidity vertical bar y vertical bar 1.3 GeV/c, vertical bar y vertical bar 1.3 GeV/c and vertical bar y vertical bar 1.3 GeV/c, vertical bar y vertical bar < 0.9) = 1.46 +/- 0.38 (stat.)(-0.32)(+0.26) (syst.) mu b. The results are compared to QCD model predictions. The shape of the p(t) and y distributions of b-quarks predicted by perturbative QCD model calculations are used to extrapolate the measured cross section to derive the b (b) over bar pair total cross section and d sigma/dy at mid-rapidity.
Keywords: Hadron-Hadron Scattering; QED RADIATIVE-CORRECTIONS; UNIVERSAL MONTE-CARLO; P(P)OVER-BAR COLLISIONS; QUARK PRODUCTION; D-SIGMA/DP(T); DECAYS; PHOTOS; MESON; Physics